The efficacy and toxicity of maintenance therapy with bevacizumab plus pemetrexed versus bevacizumab/pemetrexed alone for stage IIIB/IV nonsquamous non‐small cell lung cancer: A meta‐analysis of randomized controlled trials. (6th October 2021) - Liu, Miaowen; Luo, Nachuan; Fang, Zige; Liu, Qiangyun; Yi, Fengming; Wei, Yiping; Zhang, Xinyi; Zhang, Wenxiong
Abstract: What is known and Objective: Whether maintenance therapy with bevacizumab (Bev) + pemetrexed (Pem) can achieve greater clinical benefits than Bev or Pem alone for stage IIIB/IV nonsquamous non‐small cell lung cancer (NSCLC) remains unclear. We assessed the antitumour effect and toxicity of maintenance Bev+Pem versus maintenance with single‐agent Bev/Pem in this meta‐analysis. Methods: Appropriate randomized controlled trials (RCTs) were screened using electronic databases (Google Scholar, PubMed, Embase, Scopus, ScienceDirect, Ovid MEDLINE, Cochrane and Web of Science). The endpoints were progression‐free survival (PFS), overall survival (OS) and adverse events (AEs). Results and discussion: We included six RCTs that contained 2, 447 patients receiving induction therapy with platinum‐based combination therapies. The maintenance therapy Bev+Pem group had prolonged PFS (HR = 0.74, 95% CI 0.69–0.80, p  < 0.00001) and OS (HR = 0.91, 95% CI 0.83–0.99, p  = 0.02) compared with the Bev/Pem group. Moreover, we further analysed the PFS rate (PFSR) and OS rate (OSR) and found that the Bev+Pem group exhibited improved PFSR‐0.5y, PFSR‐1y, PFSR‐1.5y, PFSR‐2y and OS‐2y, with preferable trends in OS‐1y, OS‐3y and OS‐4y compared with the Bev/Pem single‐agent maintenance therapy. In addition, subgroup analyses indicated that the Bev+Pem group had greater PFS and OS among patients aged <65 years, patients with an Eastern Cooperative Oncology Group (ECOG) score of 0, and patients who never smoked. Regarding adverse events (AEs), the Bev+Pem group exhibited an increased occurrence of anaemia, fatigue, thrombocytopenia and anorexia. What is new and Conclusion: For stage IIIB/IV nonsquamous NSCLC patients, maintenance therapy with Bev+Pem offers an increased survival outcome (PFS, OS) compared with monotherapy. However, the increased incidence of AEs should not be neglected. Abstract : This study was the first meta‐analysis that compared maintenance bevacizumab/pemetrexed and maintenance with bevacizumab/pemetrexed alone for stage IIIB/IV nonsquamous non‐small cell lung cancer. The results suggested that maintenance therapy with Bev+Pem offers an increased survival outcome (PFS, OS) compared with monotherapy. However, the increased incidence of AEs should not be neglected.